Revitalisasi Kuliner Bingen Palembang Sebagai Sarana Pelestarian Kuliner Tradisional Palembang Dan Peningkatan Kualitas Ekonomi Masyarakat Seberang Ulu II Kota Palembang - Putri Anindhita Faradila; fitriya Fitriya; abdul Basyith (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The city of Palembang is the capital of the Province of South Sumatra. The city of Palembang is a city where there is a kingdom that controls the Archipelago and the Malay Peninsula in the 9th Century, namely the Sriwijaya Kingdom. The history of the city of Palembang is inseparable from a variety of multi-ethnic Javanese, Malay, Chinese, Arabic and other ethnic groups which gave birth to multi-cultural arts and traditional foods typical of the city of Palembang. Traditional in Palembang language is called the word